2017
DOI: 10.2340/16501977-2279
|View full text |Cite
|
Sign up to set email alerts
|

Determining the cut-off value for knee extensor strength for identifying independence in gait in chronic stroke survivors

Abstract: These cut-off values could help to identify stroke survivors who are no longer independent in gait because of decreasing knee extensor strength on the paretic and non-paretic sides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In addition, non-ambulatory chronic stroke survivors have decreased muscle mass and increased intramuscular fat of the quadriceps compared with ambulatory survivors [ 14 ]. The quadriceps muscle strength of the paretic and non-paretic limbs in non-ambulatory chronic stroke survivors is also lower than that of ambulatory survivors [ 15 ]. In other words, although the quadriceps of both limbs in non-ambulatory chronic stroke survivors show remarkably decreased muscle mass and muscle strength and increased intramuscular fat compared with ambulatory survivors, our findings suggest that the relationships among muscle mass, intramuscular fat, and muscle strength are similar among the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, non-ambulatory chronic stroke survivors have decreased muscle mass and increased intramuscular fat of the quadriceps compared with ambulatory survivors [ 14 ]. The quadriceps muscle strength of the paretic and non-paretic limbs in non-ambulatory chronic stroke survivors is also lower than that of ambulatory survivors [ 15 ]. In other words, although the quadriceps of both limbs in non-ambulatory chronic stroke survivors show remarkably decreased muscle mass and muscle strength and increased intramuscular fat compared with ambulatory survivors, our findings suggest that the relationships among muscle mass, intramuscular fat, and muscle strength are similar among the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed remarkably decreased muscle mass and increased intramuscular fat of the quadriceps of the paretic and non-paretic limbs in non-ambulatory chronic stroke survivors compared with those in ambulatory chronic stroke survivors [ 14 ]. Quadriceps muscle strength of the paretic and non-paretic limbs has also been shown to be lower in non-ambulatory than in ambulatory chronic stroke survivors [ 15 ]. Considering these findings, and given that the function of the paretic lower extremity does not recover sufficiently in the chronic phase [ 16 ], increasing muscle mass and decreasing intramuscular fat may be important for improving the muscle strength of the quadriceps in non-ambulatory chronic stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…We used the mean grayscale within the RF region of interest in the quadriceps as an index of the ratio of intramuscular fat in the skeletal muscle because greater EI values are reported to indicate an increased proportion of adipose tissues in a given skeletal muscle [15][16][17]. Reduced MT values and greater RF muscle EI val-ues at the anterior mid-thigh are reported to be related to decreased isometric MVC strength during knee extension and reduced physical function [8,9,19].…”
Section: Ultrasonographic Assessmentmentioning
confidence: 99%
“…These changes can induce locomotor dysfunction after stroke [6,7]. Quadriceps strength is closely related to gait independence [8,9]. A recent study revealed that gait independence after stroke can be explained by maximal voluntary contraction (MVC) strength during isometric knee extension produced by the quadriceps, pro-DOI: 10.1159/000507548 posing a cutoff value of MVC strength for explaining gait independence [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation